A Life Cycle Assessment (LCA) Approach on the Production of Sago Sucker for Cultivation - SULAIMAN, NAJWA; KHAIRUDDIN, NIK SASHA KHATRINA; ISMAIL, MAIZAN; YEOH , CHEE BENG; AHMAD BUSTAMAM, FARAH KHUWAILAH (Borneo Journal of Resource Science and Technology, 2021)
Sago palm is one of the commodities being cultivated and traded in Malaysia for its high starch content. Sago seedling, or commonly referred to as sucker, is the planting material for sago cultivation. This paper discusses the life cycle assessment approach for the calculation of life cycle inventory for the production of one sago sucker. In this study, the functional unit is defined as one sago sucker. The process starts from the reception of suckers from suppliers, raft preparation, planting sago suckers in rafts, fertilization, and ends with transportation of the suckers to the plantation. Interviews and data verification were done on-site at the Crop Research and Application Unit (CRAUN) Sungai Talau Research Station. LCI data showed that water was the main input for the production of sago sucker, followed by diesel for transportation, pesticides, and fertilisers. The outcome of this study provides a basis or guideline to planters in implementing sago best agricultural practices for the production of sustainable sago.